CCQM-K138 : Determination of aflatoxins (AFB1, AFB2, AFG1, AFG2 and Total AFs) in Dried Fig. Key Comparison Track C. Final Report November 2018 - Goren, A. C. (2019)
Nine NMI/DI participated in the CCQM Organic Analysis WG Track C Key Comparison CCQM-K138 Determination of aflatoxins (AFB1, AFB2, AFG1, AFG2 and Total AFs) in Dried Fig. Participants were requested to evaluate the mass fractions expressed in ng/g units, of aflatoxins B1, B2, G1, G2 and total aflatoxin in a dried fig. Aflatoxins are part of the mycotoxin family of contaminants which are a major issue for the food production industry internationally. The CCQM-K138 results ranged from 5.17 to 7.27 ng/g with an %RSD of 10.47 for AFB1, ranging from 0.60 to 0.871 ng/g with an %RSD of 11.69 for AFB2, ranging from 1.98 to 2.6 ng/g with an %RSD of 10.36 for AFG1, ranging from 0.06 to 0.32 ng/g with an %RSD of 35.6 for AFG2, and ranging from 8.29 to 10.31 ng/g with an %RSD of 7.69 for Total AFs. All participants based their analyses on Liquid Chromatography, seven utilizing LC-MS/MS with labelled internal standards and two utilizing HPLC-FLD. Linear Pool estimators were used to assign the Key Comparison Reference Values (KCRVs) for B1, B2, G1, G2 and total aflatoxins. Successful participation in CCQM-K138 demonstrates the following measurement capabilities in determining mass fraction of organic compounds, with molecular mass of 100 g/mol to 500 g/mol, having high polarity (pKow > -2), in mass fraction range from 0.05 ng/g to 500 ng/g in dried food matrices. It was noted that the results for CCQM-K138 represent a highly challenging set of measurands and involve very low level measurement of complex analytes in a situation where there is very limited availability of appropriate calibration materials. Due to the variability in results the degrees of equivalence for these analytes were reasonably large and this will need to be taken into consideration in the assessment of proposed CMCs.